(3WHbGJ GdMfajIs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdeMOK eMji GdOjf YHO GdbGOQ Hf eMeO Hf eMeO Hf aVd Gddg Hf SGde Hf CHj GdhaGA GdbQTi GdMfai s
(3BNQgG (B:s
(3GfJgi HMeO Gddg JYGdi hMSf Jhajbg hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B168 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs